The Relationship Between Breastfeeding Mothers' Knowledge and the Provision of MP-ASI in Infants - Sri Marliani Dondo; Nila Widya Keswara; Rani Safitri (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2025)
Complementary feeding is an important stage in infant growth and development. Lack of maternal knowledge regarding the appropriate timing and type of complementary feeding can have a negative impact on infant nutritional status, including the risk of malnutrition and stunting. This study aimed to analyze the relationship between breastfeeding mothers' knowledge and infants' complementary feeding practices. This study used a cross-sectional design with a sample size of 25 mothers selected using simple random sampling technique. Data were collected through a questionnaire that measured mothers' knowledge level about complementary feeding and their feeding practices. Data were analyzed using the Spearman Rank test using SPSS version 22, with a significance level of p < 0.05. The results showed that the majority of mothers were 20-35 years old (48%) and had primary education (68%). A total of 44% of mothers had a low level of knowledge about complementary feeding, and 55% of mothers gave complementary feeding before the baby was 6 months old. Spearman correlation analysis showed a weak association between mothers' knowledge level and complementary feeding practices (p = 0.078; r = 0.359). Although not statistically significant, the direction of the association suggests that the better the mothers' knowledge, the more likely they are to provide complementary foods as recommended. The conclusion of this study emphasizes the importance of educational interventions to improve mothers' understanding of complementary feeding to reduce inappropriate feeding practices. Community-based education programs can be an effective strategy to increase maternal awareness and ensure appropriate complementary feeding for infants.